Exploring the Identity Development, Metrosexual Masculinity, and Metrosexual Experience throughout Purchase Journey in Malaysian Context - BANO, SOBIA (2018)
Metrosexual is a phenomenon of the 21st century, which challenged the conventional notion of man to a soft man with appealing and pleasant appearance. Men have started to distance themselves from the traditional masculinity by enjoying the disposable income on a gym membership, hair salon, body depilation, and spending money on designer wear. Literature acknowledges that phenomena are growing, still not studied extensively. To fill the gap in the research, qualitative study is employed to explore the role of early experience and consumption practices on the identity formation by combining the elements of Erikson identity theory and Marcia identity status; personality traits of metrosexual masculinity; and the metrosexual experience throughout the purchase journey.